# (3x+7+3x+7)+(4x-2+4x-2)=

## Simple and best practice solution for (3x+7+3x+7)+(4x-2+4x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (3x+7+3x+7)+(4x-2+4x-2)= equation:

Simplifying
(3x + 7 + 3x + 7) + (4x + -2 + 4x + -2) = 0
Reorder the terms:
(7 + 7 + 3x + 3x) + (4x + -2 + 4x + -2) = 0
Combine like terms: 7 + 7 = 14
(14 + 3x + 3x) + (4x + -2 + 4x + -2) = 0
Combine like terms: 3x + 3x = 6x
(14 + 6x) + (4x + -2 + 4x + -2) = 0
Remove parenthesis around (14 + 6x)
14 + 6x + (4x + -2 + 4x + -2) = 0
Reorder the terms:
14 + 6x + (-2 + -2 + 4x + 4x) = 0
Combine like terms: -2 + -2 = -4
14 + 6x + (-4 + 4x + 4x) = 0
Combine like terms: 4x + 4x = 8x
14 + 6x + (-4 + 8x) = 0
Remove parenthesis around (-4 + 8x)
14 + 6x + -4 + 8x = 0
Reorder the terms:
14 + -4 + 6x + 8x = 0
Combine like terms: 14 + -4 = 10
10 + 6x + 8x = 0
Combine like terms: 6x + 8x = 14x
10 + 14x = 0
Solving
10 + 14x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10' to each side of the equation.
10 + -10 + 14x = 0 + -10
Combine like terms: 10 + -10 = 0
0 + 14x = 0 + -10
14x = 0 + -10
Combine like terms: 0 + -10 = -10
14x = -10
Divide each side by '14'.
x = -0.7142857143
Simplifying
x = -0.7142857143`